Efficient Test Compression Technique Based on Block Merging - El-Maleh, A. H. (2008)
Test data compression is an effective methodology for reducing test data volume and testing time. The author presents a new test data compression technique based on block merging. The technique capitalises on the fact that many consecutive blocks of the test data can be merged together. Compression is achieved by storing the merged block and the number of blocks merged. It also takes advantage of cases where the merged block can be filled by all 0s or all 1s. Test data decompression is performed on chip using a simple circuitry that repeats the merged block the required number of times. The decompression circuitry has the advantage of being test-dataindependent. Experimental results on benchmark circuits demonstrate the effectiveness of the proposed technique compared with other coding-based compression techniques.